Sri Lanka : First and Second Reviews Under the Stand-By Arrangement and Requests for Waiver of Performance Criterion and for Extension of the Arrangement-Staff Report; Staff Statement; and News Brief on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2002)
This paper assesses Sri Lanka's First and Second Reviews Under the Stand-By Arrangement (SBA) and Requests for Waiver of Performance Criterion and for Extension of the Arrangement. The program supported by the current SBA approved in April 2001 achieved its initial objective of halting reserve losses. However, political and economic developments complicated economic policymaking during the second half of 2001 and led to a hiatus in the SBA. Despite the risks, the government's strong commitment to prudent financial policies, and the actions taken to initiate key structural reforms, merit continued IMF support.